Targeting Emerging and Untapped Markets : Rethinking Market Intelligence Decision Framework - Sarangi, Subrat; Pattnaik, Subhra (Prabandhan: Indian Journal of Management, 2018)
De-growth and stagnation in the developed world has led firms to target emerging and untapped economies for future sustainability. African and Latin American countries have attracted both large and small companies to set up operations and fuel growth. While these markets pose growth opportunities, it is a challenge, especially for smaller firms, to arrive at a go-no-go decision given the paucity of quality documented information available on such markets. Business environment assessment is half baked as traditional sources of information are limited. Firms are forced to take ad-hoc decisions based on the documented information available from analyst reports, published databases or handbooks, and trade journals. This paper addressed the gap by suggesting a framework for informed decision making on market entry. The Market Intelligence Information framework links the conventional information sources with other undocumented and unconventional formats of market intelligence through external business partners, social media and blogs, family networks, and third party market intelligence firms. Based on the framework, firms targeting untapped markets shall be able to take informed decisions and formulate market entry strategy due to better quality and variety of market intelligence. Contribution of the paper has rich managerial implications along with theoretical contribution on business environment assessment for internationalization.